Impact of predicted climate change on energy demand for air treatment in ventilation for Wrocław - Kwiecień, Dariusz; Kowalski, Piotr (Instal, 2024)
The article presents the influence of forecasted climate changes on the energy demand for air treatment, based on the example of a ventilation system designed to maintain the assumed temperature and minimum relative humidity in a room. Changes in the year-round energy demand for heating, humidification, cooling and dehumidification of air were calculated. The analyzes were based on RCP2.6, RCP4.5 and RCP8.5 scenarios describing future climate changes, developed for Wroclaw for a period of two generations – until 2080. Due to the low probability of fulfilling the RCP2.6 forecast, it was considered a baseline, while the RCP4.5 and RCP8.5 forecasts, due to expected climate changes, were adopted as relatively optimistic and pessimistic, respectively. The forecast climate change determines in the coming decades a decrease in the energy demand for heating and humidification and an increase in the energy demand for cooling and dehumidification. It is also predicted that there will be a greater risk of not meeting the assumed humidity conditions in the room. The increase in the energy demand for air cooling shows a greater increase than the change in outdoor air temperature alone. For positive heat gains in the room (∆t = 3 K, ∆t = 6 K), an increase in energy demand for cooling and dehumidification in the range of 35% (for RCP4.5) to as much as 100% (for RCP8.5) can be expected in 2080 compared to the demand in 2020, with a simultaneous reduction in the time it takes to ensure indoor humidity conditions at the required level.